Perinatal maternal depression and cortisol function in pregnancy and the postpartum period: a systematic literature review - Seth, Sunaina (BMC Pregnancy Childbirth, 2016)
BACKGROUND: Perinatal depression has a significant impact on both mother and child. However, the influence of hormonal changes during pregnancy and the postpartum period remains unclear. This article provides a systematic review of studies examining the effects of maternal cortisol function on perinatal depression. METHOD: A systematic search was conducted of six electronic databases for published research on the relationship between cortisol and perinatal depression. The databases included; MEDLINE complete, PsychINFO, SCOPUS, Psychology and Behavioural Sciences, Science Direct and EBSCO, for the years 1960 to May 2015. Risk of bias was assessed and data extraction verified by two investigators. RESULTS: In total, 47 studies met criteria and studies showed considerable variation in terms of methodology including sample size, cortisol assays, cortisol substrates, sampling processes and outcome measures. Those studies identified as higher quality found that the cortisol awakening response is positively associated with momentary mood states but is blunted in cases of major maternal depression. Furthermore, results indicate that hypercortisolemia is linked to transient depressive states while hypocortisolemia is related to chronic postpartum depression. DISCUSSION AND CONCLUSION: Future research should aim to improve the accuracy of cortisol measurement over time, obtain multiple cortisol samples in a day and utilise diagnostic measures of depression. Future studies should also consider both antenatal and postnatal depression and the differential impact of atypical versus melancholic depression on cortisol levels, as this can help to further clarify the relationship between perinatal depression and maternal cortisol function across pregnancy and the postpartum period. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-016-0915-y) contains supplementary material, which is available to authorized users.